(3MGTjI Ydi GdeYGdes - (3GdTQhGfj, GdCUagGfj, GdeTgOj, eMeO Hf GdMSf, J (B1098(3g`s
(3ChdgG (B:s
(3Gdabg aj GddZI(B: (3Gdage(B. (3GfeG GHJOC HJYQja Gdabg Ohf CUhd Gdabg(B...s
(3BNQgG (B:s
(3Ydi YOe LhGR GdfSN (B... (3GdYed HGdefShN hCdG jchf fSNG Ydi GdJbOjQjf cPG bjd hdYdg CLed(B...s
(3JHUQI GdYfhGf (B:s
(3MGTjI Ydi GdeYGdes
(3JHUQI GdeDda (B:s
(3hjYQa H`(B: (3edG ejQRG, hGdaGVd GdTQhGfj(B. (3jQhi aj JGQjN haGJg(B: 1099(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B221s
Keywords: (3CUhd Gdabgs